2023
DOI: 10.1186/s12903-023-03064-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of fully guided virtual implant planning software among dental undergraduate students

Abstract: Background Fully guided implant surgery as a technique is gaining popularity. It has been observed that use of surgical guides improves precision and predictability for dental implant placement. However, like any other newer technology, the acceptance of fully guided dental implant technology among users is based upon its perceived usability. This study aimed at evaluating the perception about using Virtual Implant Planning Software (VIPS) among undergraduate dental students at the university o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The practice mode permitted multiple repetitions which enhances content acquisition, retention, and mastery [ 16 ]. Instructors could use the VIPS to monitor students’ learning time, progress, and content mastery to advance teaching effectiveness [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice mode permitted multiple repetitions which enhances content acquisition, retention, and mastery [ 16 ]. Instructors could use the VIPS to monitor students’ learning time, progress, and content mastery to advance teaching effectiveness [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with conventional evaluation techniques, the virtual simulation teaching platform is more pragmatic and precise and measures training, and evaluation and consistently make improvements according to the instructor feedback [ 16 , 17 ]. Recently, virtual simulation has been utilized in dental education as an adjunctive to the conventional skill training curriculum to train dentists before interacting with real patients [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chemotactic function performed by the alpha granules of platelets, particularly by the growth factors contained therein (TGF beta and PDGF), and neo-angiogenic action determine the course of the differentiation of the still-undifferentiated osteoblasts and neo-angiogenesis; these effects serve as the basis of the formation of new bone, whose quality and quantity depend on the outcomes of clots and the platelets they contain. A particularly important role is played by the surgical planning of implant positioning; many authors [46][47][48] have demonstrated how perfect knowledge of the bone anatomy and the consequent guided surgical planning can improve the optimal selection of the implant, reduce surgical times, obtain optimal prosthetic results, and, in what is probably the most important aspect, improve the attitudes of patients to implant surgery. In the future, it will be possible to make complete libraries relating to the Rex implant available to clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants are widely used in dentistry for prosthetic rehabilitation. [1][2][3][4] Peri-implantitis, a common complication in implant dentistry, immensely affects osseointegration and is one of the major causes of implant failure. [5][6][7] Peri-implantitis is defined as an irreversible pathological condition of the peri-implant tissues exhibiting inflammation of the mucosa and progressive loss of bone support.…”
Section: Introductionmentioning
confidence: 99%